ANALISIS BIAYA PERAWATAN DAN PEMELIHARAAN JALAN PERKERASAN KAKU DI KABUPATEN BENGKALIS - Wahyuni, Sri; Gunawan, Gunawan (Politeknik Negeri Bengkalis, 2024)
Along with the increasing population in bengkalis Regency, especially on Jalan Bunga Raya, Bantan District, it is necessary to have safe, comfortable and efficient road conditions to support the economic needs of the community. Jalan Bunga Raya Bantan District is a public road that connects between service centers, with these conditions it is necessary to have good pavement conditions so as not to disturb the comfort of road users.Â The method used in calculating maintenance over the life of the plan, which is 20 (twenty) years in the future, is Life Cycle Cost (LCC). Life Cycle Cost (LCC) is a method used to obtain alternatives to various possibilities in decision making and describe the present and future value of a road construction development, namely by calculating and considering inflation and interest rates.The initial construction cost that must be incurred is Rp.1,445,028,545.00. Routine maintenance costs amounted to Rp 95,906,000.00 and Periodic maintenance costs amounted to Rp 1,952,246,000.00. The total maintenance cost by calculating with Average Inflation is IDR 8,523,122,444.82. The total percentage of Initial Cost is 14.496% and the percentage of Maintenance Cost is 85.504%. The analysis results show that the NPV with the average bank interest rate (4.5%) is Rp 4,805,301,346.75. At the highest bank interest rate (5.6%), the NPV is Rp 9,039,238,798.56, while at the lowest bank interest rate (3.5%) the NPV reaches Rp 6,465,780,661.43.